ANALISIS STRUKTUR MUSIK IRINGAN TARI JONGGAN DI DESA SEBENTE KECAMATAN TERIAK KABUPATEN BENGKAYANG - Selmen Selmen; Nurmila Sari Djau; Asfar Munir (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe background of this research is the analysis of the structure of the musical accompaniment of the Jonggan dance in Sebente Village, Shout District, Bengkayang Regency. The formulation of the problem in this study is 1) How is the analysis. the structure of the musical accompaniment of the Jonggan dance in Sebente Village, Shout District, Bengkayang Regency, 2) How to design the implementation of the analysis of the structure of the Jonggan dance music structure in Sebente Village, Shout District, Bengkayang Regency in the world of education. The method used in this study is a descriptive method with a qualitative form and uses an ethnomusicological approach. the data sources in this study were Ranje, Aloysius Ngansen, and Tulen. The data in this study were the results of observations, interviews, and documentation regarding the structure of the musical accompaniment of the Jonggan dance. Data collection techniques used observation, interviews and documentation techniques. The data validity test technique used triangulation technique.Keywords: Jonggan dance accompaniment music structure.